Patents & trademarks - Wheeler, Peter; Scull, Tony (Executive Business Club, 1993)
This British programme examines the protection of intellectual property through patents and trademarks. The programme shows how they protect new ideas and ensure that even small firms are able to show a return from their inventions and innovations.